Content validation and use of mothers on respect index to determine levels of respectful maternity care among women facing disadvantage, birthing in the Top End of the Northern Territory: a cross-sectional study - Bowden, Emily Rebecca; Toombs, Maree R.; Williams, Robyn L.; Chang, Anne B.; Richards, Deborah; Porte, Meredith; Yerkovich, Stephanie; McCallum, Gabrielle Britt (Frontiers in Global Women's Health, 2025)
IntroductionAlthough recognised as important, few validated tools are available to measure respectful maternity care. In Australia, First Nations, migrant and refugee women have fewer antenatal attendances and poorer outcomes compared to others, with disrespectful maternity care a known barrier to care-seeking. Our primary aim was to determine content validity of the Mothers on Respect index (MORi) for use with women facing disadvantage birthing in the Top End of the Northern Territory. Our secondary aim was to determine the extent of respectful maternity care amongst these women in our setting.MethodsFifteen First Nations women participated in an iterative process, rating and commenting on the original MORi items using content-validation-index for items. 195 First Nations, migrant, refugee women subsequently completed the content-validated MORi, within 12-months postpartum.ResultsContent validity was established for all items; The overall median MORi score was high at 78 [interquartile range (IQR) 72–83]. Migrant women had the highest median score of 80 (IQR 76–83), remote-living First Nations women had the lowest at 63.5 (IQR 55–76). There were no significant differences across antenatal attendance, educational attainment, or primary caregiver.DiscussionOverall, high levels of respectful maternity care were observed. First Nations women from remote communities, and refugee women within some domains, experienced lower levels of respect than others, perhaps resulting from ongoing systemic disadvantage. MORi content-validity was established for First Nations Australians, migrant and refugee women with disparity between cohorts observed. Continuity-of-carer, increased access to interpreters, and companion of choice may address some of these disparities.